Ships on the Wall: Retracing African Trade Routes from Marseille, France - Helen A. Regis (Genealogy, 2021)
With this essay on decolonizing ways of knowing, I seek to understand the phantom histories of my father’s French family. Filling in silences in written family accounts with scholarship on Marseille’s maritime commerce, African history, African Diaspora studies, and my own archival research, I seek to reconnect European, African, and Caribbean threads of my family story. Travelling from New Orleans to Marseille, Zanzibar, Ouidah, Porto-Novo, Martinique and Guadeloupe, this research at the intersections of personal and collective heritage links critical genealogies to colonial processes that structured the Atlantic world. Through an exploration of family documents, literature, and art, I travel the trade routes of la Maison Régis.